Prediction of Biochemical Recurrence After Radical Prostatectomy Based on Preoperative 68Ga-PSMA-11 PET/CT - Qiu, Xuefeng; Chen, Mengxia; Yin, Haoli; Zhang, Qing; Li, Haoyang; Guo, Suhan; Fu, Yao; Zang, Shiming; Ai, Shuyue; Wang, Feng; Guo, Hongqian (Frontiers in Oncology, 2021)
Purpose This study was designed to investigate the prognostic role of preoperative 68Ga-PSMA-11 PET/CT in predicting biochemical recurrence (BCR) of localized prostate cancer (PCa) after radical prostatectomy (RP). Methods A total of 77 biopsy-confirmed PCa patients with 68Ga-PSMA-11 PET/CT prior to RP were included. A PSMA-ligand PET/CT-based risk model with SUVmax, maximum diameter of the index tumor and T stage was developed for prediction of 2-year BCR using Cox regression analysis. Also, the efficacy of the developed risk model was compared with European Association of Urology risk stratification (D’Amico) and the Cancer of the Prostate Risk Assessment (CAPRA) score. C-index and calibration plot were used to assess discrimination and calibration with internal validation. Results With a median follow-up of 25 months, 23 (29.9%) patients experienced BCR within 2 years after RP. Patients experienced BCR had a significant higher PSA at diagnosis (p<0.001), a higher ISUP grade of biopsy (p=0.044), as well as a higher ISUP grade (p=0.001), a higher possibility of T3 diseases (p=0.001) and positive margin (p=0.008) on postoperative pathology. SUVmax, maximum diameter of the index tumor and T stage on preoperative PSMA-ligand PET/CT were significantly associated with BCR (all p<0.01). PSMA-ligand PET/CT-based risk model had a superior discrimination (c-index 78.5%) and good calibration at internal validation. The efficacy of this model in predicting 2-year BCR after RP was better, compared with CAPRA (c-index 66.3%) and D’Amico (c-index 66.2%). The addition of the PSMA-ligand PET/CT-derived variables also improved the efficacy of the existing models in predicting 2-year BCR (C-index of 78.9% for modified CAPRA and 79.3% for modified D’Amico, respectively). Conclusion A PSMA-ligand PET/CT-based risk model showed good efficacy in predicting 2-year BCR after RP, which needed to be validated by further prospective studies.